THE ROLE OF CIVIL SOCIETY IN THE FIGHT AGAINST CORRUPTION IN NIGERIA’S FOURTH REPUBLIC: PROBLEMS, PROSPECTS AND THE WAY FORWARD - Patrick Ukase; Bem Audu (European Scientific Journal, ESJ, 2015)
Using a historical perspective, this essay historicizes and analyses the role and contributions of Civil society towards the entrenchment of democracy, good governance, and the rule of law in Nigeria, but much importantly in the eradication of corruption. The paper argues that the country witnessed the collapse of most institutions-especially institutions that are charged with the responsibility of checking corruption during the long years of military adventurism into the nation’s political space. Given the zeal and propensity with which civil society contributed in dismantling the previous military regimes, it was also expected that they would serve as a critical agent in the fight against corruption. The paper contends that even though civil society have been at the centre of the fight against corruption and the enthronement of democracy, good governance, and the rule of law, especially in the face of weak anti-corruption institutions, they have been confronted with a lot of challenges. While examining the various ramifications of the challenges confronting civil society in Nigeria (these include internal and external), the paper stresses the need to strengthen civil society groups in Nigeria if the country is to make any significant breakthrough in its fight against corruption and the enthronement of democracy and good governance in the fourth republic.